Specific surface area of combustion emitted particles: Impact of primary particle diameter and organic content. (November 2019) - Ouf, F.-X.; Bourrous, S.; Vallières, C.; Yon, J.; Lintis, L.
Abstract: Specific surface areas of particles produced at small-scale diffusion flame burners and also in pilot and large-scale fires involving complex fuels are reported and compared. Specific surface area SBET is determined by BET (Brunauer-Emmett-Teller) analysis and also according to previously developed approach STEM relying on the primary sphere based on TEM (Tansmission Electron Microscopy) images analysis. True density is also determined and the respective influences of primary particle diameter (Dpp ) and organic carbon to total carbon ratio (OC/TC) are discussed. The present study is the first to propose a careful comparison between TEM and BET specific surface areas of 20 different samples of carbonaceous particles emitted under realistic fire conditions and to bring validity range for such TEM based approach. For samples containing low and moderate OC content (less than 20%), a good agreement between STEM and SBET is reported (within ± 20% for a confidence interval of 95%), confirming the significant influence of primary particle diameter and the relevance of a purely geometrical description of the surface specific area of soot particles. For larger OC/TC, such approach fails to predict the particles specific surface area within a reasonable confidence interval. Graphical abstract: Image 1 Highlights: First determination of specific surface area of fire soot samples. BET, TEM and OC/TC analysis of 20 samples. Specific surface area BET decreases with increasing OC/TC ratio. Comparison of specific surface area measured by BET (SBET ) and TEM (STEM ) analyses. Good agreement between SBET and STEM for OC/TC ratio up to 20%.